Front Cover: Magneto‐Structural and Computational Study of a Tetranuclear Copper Complex Displaying Carbonyl–π Interactions (Eur. J. Inorg. Chem. 47/2018). Issue 47 (10th December 2018) - Kochem, Amélie; Faure, Bruno; Bertaina, Sylvain; Rivière, Eric; Giorgi, Michel; Réglier, Marius; Orio, Maylis; Simaan, A. Jalila
Abstract : The Front Cover shows a tetranuclear metal complex consisting of four copper(II) ions bridged by alkoxo linkers. Intramolecular noncovalent carbonyl‐π interactions were found to be operative within the system. Computational studies (DFT) were conducted to rationalize the magnetic interactions in the tetranuclear entity and to determine the structural role of the noncovalent interactions. The authors thank Dr. Sylvain Bertaina for his assistance in designing the cover illustration. More information can be found in theFull Paper by M. Orio, A. J. Simaan et al. For more on the story behind the cover research, see theCover Profile .